The Effect of Mercuric Exposure on Oxidative Stress and Enzymatic Antioxidant Defense System - Mohammed, I.A.; AL-Jobouri, M.I.; AL-Taie, W.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Throughout the centuries, several incidents of mercury toxicity have been reported. Mercury is found in many industries such as battery, thermometer and barometer manufacturing, in the agricultural industry is used in fungicides and in medicine, mercury is used in dental amalgams. An important mechanism involved in cellular injury is induced by exposure to different forms of mercury involves in the induction of oxidative stress.      This study was conducted on non-smoker, male working in a chloroalkali plant for different periods, all workers were not suffering from chronic disease. Healthy non-smoker males that are not exposed, matched age were used as controls(C), workers aged (22-61) years, they were divided into three groups: G1: workers with exposed period less than 10 years, G1 < 10 years. G2: workers with exposed period (10-19) years . G3: included workers with exposed period more than 19 years, G3 > 19 years.     The result we had through examining the different parameters led us to add another group which included individuals with high mercury levels regardless the occupation period, in this group we found high significant changes in the defense system parameters that we measured.      This study showed an elevation in MDA levels in all workers group, specially those with high level mercury , which were 9.31, 12.78, 12.99, 14.73, and 18.11nmol/dl for C, G1, G2 , G3 ,and high level mercury workers respectively .      No alteration was found in SOD activity in erythrocyte (0.67, 0.73, 0.72, and 0.77 U/g.Hb) for C, G1, G2 and G3 respectively.       There were highly significant decrease in catalase activity (P < 0.001) in erythrocyte of all worker groups compared to normal control. The values were (1.5, 0.8, 0.88, 0.815 and 0.45 U/gm/Hb) for C, G1, G2, G3 and G4 respectively. While there were high elevation in glutathione S-transferase activity in worker groups compared to control (P < 0.001) and values were (1.85, 2.589, 2.441, 2.776 and 3.2 U/gm.Hb) for C, G1, G2 and G3 respectively.